Ukraine’s position in the European Union’s Neighbourhood Policy (Economic and Political Thought, 2017)
The objective of the present paper is to discuss Ukraine’s position in boththe European Neighbourhood Policy (established in 2004) and the EasternPartnership project based on the policy. The Orange Revolution of 2004 andevents of 2013/2014 in Ukraine labeled the Euromaidan indicated that theEuropean direction of the country is of critical importance for a considerablepart of Ukrainian society and political elites. Integration with the EU presentsa necessity for a civilizational choice for Ukraine. The fact that, of all stateslocated on the EU’s eastern border, it is Ukraine which poses the greatestchallenge, is noteworthy. Ukraine’s geopolitical and geoeconomic positionmake it a key player both for the EU and Russia as well.